Improvement in breast cancer survival across molecular subtypes in Hungary between 2011 and 2020: a nationwide, retrospective study - Darida, Miklós; Rubovszky, Gábor; Kiss, Zoltán; Székely, Borbála; Madaras, Balázs; Horváth, Zsolt; Kocsis, Judit; Sipőcz, István; Várnai, Máté; Balogh, Éva; Kovács, Krisztina; Buga, Viktória; et al. (Frontiers in Oncology, 2025)
BackgroundDespite well-documented clinical differences across breast-cancer (BC) molecular subtypes and relevant changes in therapeutic interventions over the past decades, there remains a significant lack of up-to-date epidemiologic data and real-world outcomes, particularly in Central and Eastern Europe.MethodsThis was a nationwide, retrospective study using the claims databases of the Hungarian National Health Insurance Fund (NHIF) that included patients who were newly diagnosed with BC between 2011 and 2020. BC subtypes were defined based on the therapies received. Overall survival (OS) and net survival rates were calculated.ResultsBetween 2011 and 2020, 74,143 patients were newly diagnosed with BC based on ICD-10 diagnostic codes in the NHIF database and 80.1% of the cases could be classified into subtypes based on therapy. The most common subtype was HER2–/HR+ BC, identified in 61.9% of patients, followed by triple negative breast cancer (TNBC) in 8.4%, HER2+/HR+ BC in 6.2%, and HER2+/HR- BC in 3.6% of cases. The proportions of TNBC and HER2+/HR+ were higher among younger patients, than in elderly cohorts. The 5-year OS of the total BC population was 74.2% in patients diagnosed between 2015–2019. Patients with TNBC had the poorest 5-year OS (TNBC: 61.4%; HER2+/HR+: 86.5%; HER2-/HR+: 79.1%; HER2+/HR–: 71.9%). Net survival rates (i.e. survival rates after adjusting the effects of other causes of death) varied across diagnostic periods and molecular subtypes. In most cases, patients diagnosed later during the study period tended to have numerically better survival rates. Patients with HER2–/HR+ BC had the most favorable net survival, with 5-year net survival exceeding 92% during the whole observation period, while TNBC patients had the lowest 5-year net survival rates ranging between 63.6% and 65.8% during the study period.ConclusionOur nationwide study describes the distribution and survival of BC patients with different subtypes based on a retrospective analysis of the health insurance fund database. There remains a significant room for improvement in the survival of more aggressive molecular subtypes including HR–/HER2+ and triple-negative BC, which are more common in younger age cohorts.